Antimicrobial Resistance Surveillance to Support Decision-Making in a High-Prevalence Region: An Evaluation - Goddard, Laura; Wozniak, Teresa M. (Frontiers in Tropical Diseases, 2021)
Despite a high use of antibiotics and a significant burden of infectious disease, ongoing monitoring and reporting of antimicrobial resistant pathogens in rural and regional Australia is insufficient. Many geographically isolated regions of Australia have limited infrastructure, resources and fall outside of surveillance reach, limiting health services’ ability to provide an early warning signal and appropriate response. To monitor trends in the development of antimicrobial resistance (AMR), identify high-risk populations and to evaluate effectiveness of control and prevention in rural and regional Australia, a subnational surveillance system termed HOTspots was developed. To promote the best use of public health resources through the development of effective and efficient surveillance systems, we evaluated HOTspots and its prototype surveillance platform for data quality, acceptability, representativeness, and timeliness. We used the Centers for Disease Prevention and Control (CDC) guidelines for evaluating public health surveillance systems and assessed the four attributes using a descriptive analysis of quantitative data and a thematic analysis of qualitative data. We report that the HOTspots surveillance system and its prototype platform effectively captures and represents AMR data across Northern Australia. The descriptive analysis of HOTspots data demonstrated some variation in data completeness but that data validity and representativeness were high. Thematic analysis of interview transcripts found that the system was acceptable, with almost all study participants identifying timeliness, online accessibility, and community representativeness as drivers for adoption of the system, and that the system provided timely data. The evaluation also identified areas for improvement and made recommendations to the HOTspots surveillance system and its associated prototype platform.